Adrenal Ganglioneuroma - Kayashta, R.; Acharya, R.; Pradhan, S.; Tuladhar, A. S.; Shrestha, A. (Kathmandu University Medical Journal, 2020)
Adrenal ganglioneuromas are rare sympathetic differentiated tumors which originate from neural crest cells. These lesions are usually discovered incidentally on imaging and tend to be hormonally silent. Preoperative diagnosis of adrenal ganglioneuroma remains extremely challenging and the gold standard treatment is adrenalectomy. There is good prognosis after surgery without recurrence. We herein report a case of adrenal ganglioneuroma in a 15 year old female who presented with complaint of abdominal discomfort. Contrast Enhanced Computed Tomography abdomen showed a large septated hypodense right suprarenal mass which was echogenic on Ultrasonography. It showed T1 hypointense and T2 hyperintense signal on Magnetic Resonance Imaging of abdomen and pelvis. Excisional biopsy and histological examination of the mass was suggestive of adrenal ganglioneuroma. This report presents the clinical and radiological data for the rare tumor which would share some experience to facilitate the diagnosis of adrenal ganglioneuroma.